Letter - Conley, G.
042-0053-001 St. Hilda's 9, Shaw Lane, Headingley, Leeds - 6. 18th May, 1938. Dr. H.B. Morgan, Medical Adviser, Transport House, Smith Square, London - SW1. Dear Dr. Morgan, I thank you for your letter, and have written to the address which you gave me. I see the point in your objections, of course, and recognise their practical value. I feel, however, that to take rejection for granted is a poor policy, and therefore thank you again for your attention to my application, and also for your advice. Yours faithfully, G. Conley 292/946/42/53